The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1186/s13567-021-00993-z
|View full text |Cite
|
Sign up to set email alerts
|

Review on PRNP genetics and susceptibility to chronic wasting disease of Cervidae

Abstract: To date, chronic wasting disease (CWD) is the most infectious form of prion disease affecting several captive, free ranging and wild cervid species. Responsible for marked population declines in North America, its geographical spread is now becoming a major concern in Europe. Polymorphisms in the prion protein gene (PRNP) are an important factor influencing the susceptibility to prions and their rate of propagation. All reported cervid PRNP genotypes are affected by CWD. However, in each species, some polymorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 137 publications
1
25
0
Order By: Relevance
“…As described above, several reports have confirmed that some Prnp polymorphisms confer relative resistance to CWD infection [18,[70][71][72][73][74][75][76][77]. Thus, one strategy to minimize CWD spreading might be to perform selective breeding to produce animals with several polymorphic variants known to decrease infection.…”
Section: Selective Breedingmentioning
confidence: 89%
See 2 more Smart Citations
“…As described above, several reports have confirmed that some Prnp polymorphisms confer relative resistance to CWD infection [18,[70][71][72][73][74][75][76][77]. Thus, one strategy to minimize CWD spreading might be to perform selective breeding to produce animals with several polymorphic variants known to decrease infection.…”
Section: Selective Breedingmentioning
confidence: 89%
“…In addition, prion protein polymorphisms (Table 1), as well as small differences on the aminoacid sequence between different cervid species, may lead to the emergence of new prion strains when animals are infected with PrP Sc carrying a mismatch sequence from host PrP C [66][67][68][69]. It is well-established that the presence of certain polymorphic variants in cervids (Table 1) may confer resistance to CWD infection [18,70,71]. For example, infection of whitetailed deer harboring rarer polymorphisms at position 95 and 96 of PrP C led to a prolonged incubation period compared to animals with more prevalent polymorphisms [72,73].…”
Section: Cwd Strain Diversitymentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the 23 and 12 bp insertion/deletion polymorphisms located in the promoter region were associated with the expression of the bovine PRNP gene and were reported to affect vulnerability to BSE ( 12 ). Furthermore, genetic polymorphisms at codons 95, 96, and 132 of the cervid PRNP gene played an important role in susceptibility to CWD in the cervidae family ( 13 15 ). Recent studies have reported that prion disease-resistant specific amino acids of PrPs, including S167 in horses and D159 in dogs, conferred resistance to conversion from PrP C to PrP Sc ( 16 , 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of the PRNP diversity in European cervid species is still limited but some studies carried out in Britain, Norway and Sweden, showed that some PRNP genetic variations can be related with CWD susceptibility/resistance [18]. The variations S225Y and P242L found in caribou/reindeer were associated to a higher risk of infection and the N138 polymorphism in fallow deer has been associated with natural resistance [12].…”
Section: Introductionmentioning
confidence: 99%